Take the money and run: making profits by paying borrowers to stay home - Giuseppe Coco; David De Meza; Giuseppe Pignataro; Francesco Reito (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
Can a bank increase its profit by subsidizing inactivity? This paper suggests this may occur, due to the presence of hidden information, in a monopolistic credit market. Rather than offering credit in a pooling contract, a monopolist bank can sort borrowers through an appropriate subsidy to inactivity. Under some conditions, sorting may avoid the collapse of the market and increases the welfare of everybody. The bank increases its profits, good borrowers benefit from lower interest rates and bad potential borrowers from the subsidy. The subsidy policy however implies a cross subsidy between contracts and this is possible only under monopoly.
Keywords: D60; D82; H71; 330